Deleterious Mutations in DNA Repair Gene FANCC Exist in BRCA1/2-Negative Chinese Familial Breast and/or Ovarian Cancer Patients - Pan, Zhi-Wen; Wang, Xiao-Jia; Chen, Tianhui; Ding, Xiao-Wen; Jiang, Xiyi; Gao, Yun; Mo, Wen-Ju; Huang, Yuan; Lou, Cai-Jin; Cao, Wen-Ming (Frontiers in Oncology, 2019)
Introduction: FANCC is reported as a novel susceptibility gene for breast cancer, however, its mutation remains unclear in Chinese population. We aimed to identify the germline mutations of FANCC in high-risk breast cancer patients in China. Methods: 255 BRCA1/2-negative Chinese familial breast and/or ovarian cancer (FBOC) patients were recruited for FANCC germline mutations screen. For whom 90 patients were detected by PCR-sequencing assay, and another 165 patients were detected by a 98-gene panel sequencing assay. The 98-gene panel sequencing assay was also used to screen other possible gene mutations for the patients with FANCC mutations detected by PCR-sequencing assay. 250 sporadic breast cancer (SBC) patients and 248 female non-cancer controls (FNCCs) were recruited for the genotyping analysis. Immunohistochemistry (IHC) analysis was used to evaluate the FANCC expression in patients with FANCC mutation. Results: We found one rare FANCC deleterious mutation (c.339G>A, p.W113X, 0.4%) and two novel nonsynonymous variants (c.51G>C, p.Q17H, 0.4% and c.758C>A, p.A253E, 0.4%) in FBOC patients, whereas none of above mutations was identified in SBC patients or FNCCs. We also found one novel synonymous variant (c.903A>G, p.A301A) existed in one FBOC patient. Besides, two nonsynonymous SNPs rs201407189 (c.973G>A, p.A325T) and rs1800367 (c.1345G>A, p.V449M), and two synonymous SNPs rs55719336 (c.816C>T, p.I272I) and rs79722116 (c.1407G>A, p.T469T) were identified in FBOC patients. Conclusion: FANCC deleterious mutations exist in Chinese FBOC patients and investigations on the penetrance and spectrum of FANCC mutations are needed to be further studied.